Design for Assembly and Disassembly of Battery Packs - Collijn, Mikaela; Johansson, Emma (My University, 2019)
Abstract Batteries are an upcoming and important part of future solutions for CO2-neutral vehicles in society. To become more environmental friendly, Volvo wants to exchange the combustion engines with electrical engines and replace the liquid fuel with batteries. Adding a part to a vehicle means it must be assembled as well as disassembled which results in a need for a product that is optimal for an assembly-line. A literature study is therefore conducted in this project to improve the understanding of methods including modularisation as well as Design for Assembly and Design for Disassembly. Batteries in general is also revised to get a better overview of what functions and parts are included in a battery in order to map its functions in an Enhanced Function-Means model. This model creates an image of how the functions and design solutions are connected to each other. Thereafter, benchmarking of internal and external batteries is performed by using the functions as guidelines, resulting in a variety of design solutions. The design solutions are assessed from an assembly, disassembly and modularity point of view to establish what solutions are of interest. Based on the evaluation, an “ideal” battery is developed with focus on the hardware, hence the housing, attachment of modules and wires, thermal system and battery management box. An assessment is made of the application of these high voltage batteries in Volvo and how design for second life should be considered. Conclusively, the results from the study describes what parts of a battery to revise for it to be easy to assembly and disassembly as well as suitable to modularise.
Keywords: Battery, Electric Vehicle, Function-Means Modelling, Modularisation; Design for Assembly, Design for Disassembly